(untitled) (Research, Society and Development, 2020)
The aim of this article was to investigate in the literature the factors associated with bruxism in university students. An integrative literature review was conducted with articles published between 2010 and 2020 in the PubMed and ScienceDirect databases, using descriptors: “Bruxism AND Higher Education” and MeSH synonyms, with the following steps: identification of articles, screening, eligibility and inclusion. Cross-sectional clinical observational studies, randomized clinical studies and longitudinal studies associated with bruxism were included. Population of studies that were not university or that did not deal with bruxism; case reports and literature reviews were excluded from the review. From a total of 1376 articles found only 15 articles were selected for the study. According to the evidence, some signs and symptoms are already proven to be associated with bruxism such as muscle pain, dental wear, as well as chronotypic profile, sleep disorders, and difficulty concentrating on the daily activities of this population. In addition, many articles associated the stress factor and other psychological comorbidities with the risk of bruxism in university students. Thus, it is observed that anxiety, depression, stress and frustration are common among witch-bruxonams and are associated with the development of this pathology, in other times, it is possible to induce that chronological preferences and nocturnal and daytime habits are also associated.